PENGARUH LOKASI , PROMOSI DAN BRAND IMAGE TERHADAP KEPUTUSAN WISATAWAN LOKAL UNTUK BERKUNJUNG KE PANTAI TANJUNG KERASAK DESA PASIR PUTIH TOBOALI - Agus Priyanto; Zufriady Zufriady (LPPM STIE PERTIBA Pangkalpinang, 2021)
This study aims to determine the effect of location, promotion, and brand image on purchasing decisions. The population in this study uses quantitative research, the data collection method that will be used in this study by using a questionnaire or questionnaire that will be filled directly by respondents Testing in this study uses SPSS, in the analysis of multiple linear regression it is known that the variable location, promotion and brand image a positive and significant effect on purchasing decisions. T-test results from location, promotion, and the brand image obtained sig <0.05 in a persistently independent variable positive effect on the dependent variable is accepted. Test results show that the independent variables jointly have a positive effect on the dependent variable accepted. The coefficient of determination (R Square) shows that location, promotion, and brand image can influence tourists' decision to point at 50.2% while the remaining 49.8% is explained by other variables outside of research capital